Morphological and Mineralogical Characterization of Coastal Soil Samples of Kanyakumari District by FT-IR, XRD, SEM/EDAX (International Journal of Scientific Research and Management (IJSRM), 2017)
Qualitative analysis was carried out to determine the major and minor constituent minerals present in coastal soil samples collected from west cost of Kanyakumari District, Tamilnadu by FT-IR, XRD and SEM/EDAX techniques. From the IR absorption band and the locations of the different peaks, the minerals were identified with the available literature. In addition to the band positions, the sharpness of bands was helpful in the identification of mineral components. Identification and estimation of mineralogical composition were carried out by XRD. XRD technique to yield more information about the minerals. FT-IR and XRD methods were non destructive and can be used in the identification of mineralogical composition. SEM analysis showed the coastal soil samples have different morphological structures like spherical (Al-Si-O), tubular (Si-O), triangular (Fe-Al-Si-O), platy (Ca-Si-O), nearly spherical (Fe-Ti-O) and irregular (Ca-Al-Si-O) shapes. Elemental analysis (EDAX) confirmed the presence of silicon in large quantities than the other oxides such as Al, Ca, Fe and Ti.